A REVIEW OF THE OECD EMPLOYMENT PROTECTION LEGISLATION INDICATOR FOR CANADA - Amine, Samir; Montreuil, Véra-Line (The European Journal of Applied Economics, 2018)
Since the early 1990s, employment protection legislation (EPL) has become a concern for public policy makers in particular with respect to its impact in terms of unemployment and productivity. Interest in this topic has been the subject of particular attention from international organizations. Indeed, these institutions have built analytical models to assess the strictness of EPL in different countries, but we find that these models are sometimes incomplete despite the wealth of information they provide. The purpose of this article is to propose the introduction of new elements to the Organization for Economic Co-operation and Development (OECD) analysis model based on the Canadian experience. We thus propose to adjust the synthetic indicator of EPL for Canada taking into account local specificities not taken into consideration by the OECD.
Keywords: Employment Protection Legislation; Synthetic Indicator; OECD; Voluntary Departure; Work-Sharing